Effect of initiating statin therapy on long-term outcomes of patients with dyslipidemia after intracerebral hemorrhage. (September 2019) - Lin, Ming-Shyan; Lin, Yu-Sheng; Chang, Shih-Tai; Wang, Po-Chang; Chien-Chia Wu, Victor; Lin, Wey-Yil; Chung, Chang-Min
Abstract: Background and aims: Intracerebral hemorrhage (ICH) has a higher mortality than ischemic stroke. Statin is beneficial for stroke, but high potency statin treatment has been associated with the risk of hemorrhagic stroke. The aim of this study was to assess the impact of initiating statin therapy after ICH on cardiovascular outcomes. Methods: Dyslipidemic patients were retrieved from the ICH population from the National Health Insurance Research Database in Taiwan. We retrospectively compared patients prescribed with and without statin treatment after ICH. Outcomes of interest were mortality, myocardial infarction, ischemic stroke, and hemorrhagic stroke during 5 years of follow-up. Results: Of 17, 980 adult patients with ICH and dyslipidemia, 8927 were eligible for analysis over the study period, including 1613 patients receiving statin therapy and 7314 patients not taking statins. After propensity score matching, the mean age was 61.2 ± 12.2 years in the statin group and 61.6 ± 13.0 years in the non-statin group. Hypertension was dominant, followed by diabetes mellitus, and the mean estimated NIHSS score was 12.9. The patients who received statin therapy were associated with lower risks of all-cause mortality (12.7% vs . 21.3%; hazard ratio [HR], 0.54; 95% confidence interval [CI], 0.45–0.65), cardiovascular death (4.0% vs . 7.1%; HR, 0.54; 95% CI, 0.39–0.75) and ICH (5.4% vs . 8.5%; HR, 0.62; 95% CI, 0.46–0.83) compared to those who did not receive statins. Conclusions: Initiating statin therapy after ICH was associated with a decreased risk of recurrent ICH and mortality for dyslipidemia patients. Graphical abstract: Image 1 Highlights: ● Early initiating statin might decrease recurrent intracerebral hemorrhage (ICH) ● Post ICH statin initiation could decrease all-cause mortality for the dyslipidemic population ● Statins with different potency or lipophilicity had similar outcomes after ICH